Chlamydial infection of the gastrointestinal tract: a reservoir for persistent infection. Issue 3 (10th July 2013) - Yeruva, Laxmi; Spencer, Nicole; Bowlin, Anne K.; Wang, Yin; Rank, Roger G.
Abstract The mechanism by which chlamydiae persist in vivo remains undefined; however, chlamydiae in most animals persist in the gastrointestinal tract (GI) and are transmitted via the fecal–oral route. Oral infection of mice with Chlamydia muridarum was previously shown to establish a long‐term persistent infection in the GI tract. In this study, BALB/c, DBA/2, and C57Bl/6 mice, infected orally with C. muridarum, were infected in the cecum for as long as 100 days in the absence of pathology. The primary target tissue was the cecum although the large intestine was also infected in most animals. A strong serum IgG and cecal IgA antibody response developed. Lymphocyte proliferation assays to chlamydial antigen on mesenteric lymph node cells were positive by day 10 and peaked on days 15–21, but the response returned to baseline levels by 50 days, despite the ongoing presence of the organism in the cecum. Because studies have shown that women and men become infected orally with chlamydiae, we propose that the GI tract is a site of persistent infection and that immune down‐regulation in the gut allows chlamydiae to persist indefinitely. As a result, women may become reinfected via contamination of the genital tract from the lower GI tract.